The Relationship between Parenting Styles and Children's Independence at Mentari Kindergarten - Fairuz Afra Rafifah; Hayani Wulandari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Parents' parenting patterns toward their children can make children useful regardless of their parents' education and have a unique impact on early childhood education. The purpose of this study is to determine the level of children's autonomy and to explain the relationship between educational models and children's development of autonomy. This method was chosen because, consistent with the name of the study, the researchers observed an association between parenting styles of independence in early childhood. Therefore, the results of the study yielded 14 samples that received the democratic parenting model, 5 independent samples, and 0 non-independent samples, while 4 samples that received the permissive parenting model were independent; Non-independent samples were 0. Those who adopted related parenting patterns were found in three independent samples, but two samples were not independent. In the 14 samples, 95% of the children were independent and 5% were not.